2016
DOI: 10.1126/science.aad3517
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant in scavenger receptor BI raises HDL cholesterol and increases risk of coronary heart disease

Abstract: Scavenger receptor BI (SR-BI) is the major receptor for high-density lipoprotein (HDL) cholesterol (HDL-C). In humans, high amounts of HDL-C in plasma are associated with a lower risk of coronary heart disease (CHD). Mice that have depleted Scarb1 (SR-BI knockout mice) have markedly elevated HDL-C levels but, paradoxically, increased atherosclerosis. The impact of SR-BI on HDL metabolism and CHD risk in humans remains unclear. Through targeted sequencing of coding regions of lipid-modifying genes in 328 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
353
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 472 publications
(383 citation statements)
references
References 77 publications
9
353
3
5
Order By: Relevance
“…Loss-of-function variants in human SCARB1 (SR-BI) were associated with increased in circulating HDL-C levels [37]. Likewise, Scarb1 mutations in mice also resulted in increased HDL-C levels [38].…”
Section: Resultsmentioning
confidence: 99%
“…Loss-of-function variants in human SCARB1 (SR-BI) were associated with increased in circulating HDL-C levels [37]. Likewise, Scarb1 mutations in mice also resulted in increased HDL-C levels [38].…”
Section: Resultsmentioning
confidence: 99%
“…While observational studies consistently report a protective association of high blood HDL‐C levels with lower CHD risk, previous MR studies show that HDL‐C is not a causal risk factor for CHD 48, 57. Furthermore, a recent study has reported that a loss‐of‐function variant in scavenger receptor BI ( SRB1 ) raises HDL‐C and increases CHD risk 58. Further studies are warranted to understand potential biological mechanisms of a PAI‐1 effect on HDL‐C and whether HDL‐C is an intermediary between the PAI‐1 and CHD associations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, additional studies in mice have established an inverse relationship between SR-BI expression and atherosclerosis, primarily via the mechanism of promoting reverse cholesterol transport (12,13). The impacts of SR-BI on human HDL metabolism were demonstrated by the identification of a loss-of-function SR-BI variant that is associated with an extremely high plasma HDL-C level (9) and identification of human SR-BI variants (14,15).…”
Section: Hplc Separation Of Serum Lipoprotein Cholesterol and Tgsmentioning
confidence: 99%
“…SR-BI is a physiologically relevant HDL receptor and plays distinct roles in plasma HDL metabolism and transhepatic cholesterol efflux in preclinical animal models and in humans (5)(6)(7)(8)(9). SR-BI mediates selective uptake of cholesterol ester from HDL particles into cells.…”
mentioning
confidence: 99%